2019
DOI: 10.1038/s41438-018-0083-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolic profiling of Vitis amurensis and Vitis vinifera during cold acclimation

Abstract: Vitis amurensis is a wild Vitis plant that can withstand extreme cold temperatures. However, the accumulation of metabolites during cold acclimation (CA) in V. amurensis remains largely unknown. In this study, plantlets of V. amurensis and V. vinifera cv. Muscat of Hamburg were treated at 4 °C for 24 and 72 h, and changes of metabolites in leaves were detected by gas chromatography coupled with time-of-flight mass spectrometry. Most of the identified metabolites, including carbohydrates, amino acids, and organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 63 publications
3
50
0
Order By: Relevance
“…These results are also different from that observed in the chilly response in grapes. However, previous studies on metabolomics also indicated that sugar metabolism likely has a substantial influence on cold tolerance (Chai et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These results are also different from that observed in the chilly response in grapes. However, previous studies on metabolomics also indicated that sugar metabolism likely has a substantial influence on cold tolerance (Chai et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Most plants can undergo cold acclimatization and acquire tolerance to extracellular ice formation in their vegetative tissues 22 . The exploration of the freezing tolerance of these species has contributed greatly to the understanding of cold stress 21,23 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, modern high-throughput expression profiling techniques, such as genomics, transcriptomics, and proteomics, have provided useful tools for better understanding the roles of genes when responding to LT stresses [3][4][5][6][7]. However, most of these studies reported about the effects of severe LT (≤10 • C) on temperate [5,[7][8][9], tropical, and subtropical [3,4,10] plants. Thus, information about the gene expression dynamics of tropical crops in response to mild (>15 • C) and moderate chilling (10-15 • C) is scarce [11,12], and the underlying molecular background is not well understood.…”
Section: Introductionmentioning
confidence: 99%